Grammatical Mistakes: What Is the Problem Now? - Ingatan Gulö; Dwi Budi Setiawan; Lita Sari (Universitas Teknokrat Indonesia, 2022)
The paper focuses on discussing the kinds of mistakes made by students in their writings. The writings of the same students have previously been analyzed from which earlier form of mistakes were found. After they have studied for semesters, how are their grammatical ability now? This was the question underlying this research. The data were collected and analyzed from qualitative perspective of research. The findings show that the students still make mistakes. However, the kinds of mistakes found were mostly new and are in different level of complexity.